Effect of transverse thoracic muscle plane block on postoperative cognitive dysfunction after open cardiac surgery: A randomized clinical trial. Issue 7 (6th March 2023) - Chen, Shibiao; Zhang, Hua; Zhang, Yang
Abstract: The transversus thoracis muscle plane (TTMP) block provides effective analgesia in cardiac surgery patients. The aim of this study was to assess whether bilateral TTMP blocks can reduce the incidence of postoperative cognitive dysfunction (POCD) in patients undergoing cardiac valve replacement. A group of 103 patients were randomly divided into the TTM group ( n  = 52) and the PLA (placebo) group ( n  = 51). The primary endpoint was the incidence of POCD at 1 week after surgery. Secondary outcome measures included a reduction of intraoperative mean arterial pressure (MAP) >20% from baseline, intraoperative and postoperative sufentanil consumption, length of stay in the ICU, incidence of postoperative nausea and vomiting (PONV), time to first faeces, postoperative pain at 24 h after surgery, time to extubation and the length of hospital stay. Interleukin (IL)‐6, TNF‐α, S‐100β, insulin, glucose and insulin resistance were measured at before induction of anaesthesia, 1, 3and 7 days after surgery. The MoCA scores were significantly lower and the incidence of POCD decreased significantly in TTM group compared with PLA group at 7 days after surgery. Perioperative sufentanil consumption, the incidence of PONV and intraoperative MAP reduction >20% from baseline, length of stay in the ICU, postoperative pain at 24 h after surgery, time to extubation and the length of hospital stay were significantly decreased in the TTM group. Postoperatively, IL‐6, TNF‐α, S‐100β, HOMA‐IR, insulin, glucose levels increased and the TTM group had a lower degree than the PLA group at 1, 3 and 7 days after surgery. In summary, bilateral TTMP blocks could improve postoperative cognitive function in patients undergoing cardiac valve replacement.